Soy and Its Isoflavones: The Truth Behind the Science in Breast Cancer - C. Douglas, Crystal; A. Johnson, Sarah; H. Arjmandi, Bahram (Anti-Cancer Agents in Medicinal Chemistry, 2013)
Epidemiological and migratory evidence suggests that dietary soy consumption can lower the risk for breast cancer. The role of soy isoflavones in cancer prevention and promotion is somewhat unclear. There are two views in terms of soy isoflavones and breast cancer. One line of evidence suggests that soy and its isoflavones have exhibited cancer-preventive properties including lengthening the menstrual cycle, altering estrogen metabolism away from cancerous compounds, and demonstrating anti-proliferative properties in vivo. On the contrary, isoflavones found in soy products are suggested to behave as weak estrogens and as such, much speculation surrounds the influence of soy and/or its isoflavones on hormone-receptor-positive cancers. The objective of this review is to present the latest knowledge regarding the role of soy and its isoflavones with the development and advancement of breast cancer, the safety of soy isoflavones for breast cancer survivors, and a comparison of the carcinogenic effects in animal models following soy isoflavone and estrogen administration. This review compares and contrasts literature in terms of the anti-cancer and cancer-promoting effects of soy isoflavones and estrogen in humans and animal models. In conclusion, current human and animal data provide evidence for several anticancer properties of soy and/or its isoflavones. Although the specific quantities and constituents responsible for the observed anti-cancer effects have not been elucidated, it appears that soy isoflavones do not function as an estrogen, but rather exhibit anti-estrogenic properties. However, their metabolism differs between humans and animals and therefore the outcomes of animal studies may not be applicable to humans. The majority of breast cancer cases are hormone-receptor-positive; therefore, soy isoflavones should be considered a potential anti-cancer therapeutic agent and warrant further investigation.
Keywords: menstrual cycle